Activated carbon dispersion as absorber for solar water evaporation: A parametric analysis. (15th May 2019) - Hota, Sai Kiran; Diaz, Gerardo
Highlights: Activated carbon is analyzed as an absorbing material to improve water evaporation from solar energy. Rayleigh, Mie, and geometric optics theories are utilized for the analysis depending on particle size. A parametric analysis is performed to analyze improvement in water evaporation rate. Abstract: Solar water evaporation has been a topic of interest in recent years due to its applications in desalination, power generation, and heating. As water is not a good absorber of light, seeding it with light-absorbing particles can enhance evaporation efficiency. Activated carbon (AC) is one such material with desirable absorption properties for this application. However, particle sizes in granular and powder activated carbon can vary significantly. In this work, AC particles of different sizes are analyzed and their effect on evaporation rate is studied. It is found that particle sizes less than or comparable to solar wavelength spectrum produce higher evaporation efficiencies under independent scattering conditions ( f v < 0.6 % ). It is also found that the solar absorption coefficient reaches between 0.98 and 0.9 for a volume fraction as low as 0.01%. The evaporation efficiency is 57.3% and 38.2% higher than for pure water evaporation for size of 80 nm and 8 μm, respectively, for a volume fraction of 0.01%. A parametric analysis is performed to identify the respective effect on evaporation rate.